Loaded Ce-Ag organic-inorganic hybrids and their antibacterial activity - Truffault, Laurianne; Rodrigues, Danilo Fernando; Salgado, Hérida Regida Nunes; Santilli, Celso Valentim; Pulcinelli, Sandra Helena (Elsevier, 2016)
There are requirements for surfaces with antibacterial properties in various technological fields. U-PEO hybrids with antibacterial properties were synthesized by the sol-gel process, incorporating combinations of cerium and silver salts at different silver molar fractions (0, 0.02, 0.05, 0.10, and 1) relative to the total amount of doped cations. The loaded hybrids were characterized by TGA, XRD, and Raman spectroscopy. Release tests were performed using UV–vis spectroscopy, and the antibacterial properties of the hybrids were studied in agar tests and turbidimetry assays. The nanostructural evolution of the hybrids during the release of the antibacterial agents was investigated by in situ SAXS. XRD results showed the presence of the AgCl crystalline phase in the loaded hybrids from a silver molar fraction of 0.05. Raman spectroscopy evidenced the interaction of silver cations with the polymeric part of the hybrid. SAXS results confirmed these interactions and showed that cerium species interacted with both organic and inorganic parts of the hybrids. The loaded U-PEO hybrids were found to release all the incorporated cerium in 1 h, while the hybrid containing 100% of silver released only 78% of the incorporated silver. All the loaded hybrids displayed antibacterial activity against the Pseudomonas aeruginosa bacterium. The antibacterial activity was found to increase with silver molar fraction. Due to its high antibacterial activity and low silver molar fraction, the loaded hybrid with silver molar fraction of 0.10 seemed to be a good compromise between efficiency, esthetic transparency, and photostability.
Keywords: Antibacterial release agent; Cerium; Organic-inorganic hybrids; Silver; Sol-gel process